2019
DOI: 10.3390/nano9050682
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Extraction of Radioactive Cesium-137 from Water via Graphene/CNT and Nanostructured Prussian Blue Hybrid Nanocomposites: A Review

Abstract: Cesium is a radioactive fission product generated in nuclear power plants and is disposed of as liquid waste. The recent catastrophe at the Fukushima Daiichi nuclear plant in Japan has increased the 137Cs and 134Cs concentrations in air, soil and water to lethal levels. 137Cs has a half-life of 30.4 years, while the half-life of 134Cs is around two years, therefore the formers’ detrimental effects linger for a longer period. In addition, cesium is easily transported through water bodies making water contaminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 104 publications
0
23
0
Order By: Relevance
“…By combining the sheets of both graphene and LDHs, the chemical reactivity of LDHs can integrate with the chemical inertness of graphene [14]. In addition, the high electrical conductivity of graphene can compensate the low electrical conductivity of LDHs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By combining the sheets of both graphene and LDHs, the chemical reactivity of LDHs can integrate with the chemical inertness of graphene [14]. In addition, the high electrical conductivity of graphene can compensate the low electrical conductivity of LDHs.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al [14] studied the photocatalytic properties of Zn-Al LDHs before and after combining with carboxyl graphene (CG) in presence of visible light. They reported that the photocatalytic activity of both pure Zn-Al LDHs and the CG/LDHs nanohybrid was not satisfactory probably because of the low photocatalytic activity of Zn-Al LDHs.…”
Section: Introductionmentioning
confidence: 99%
“…However, some of these complex systems may require a careful control of their preparation method, are time consuming and this often leads to high production costs and limited applicability of the materials in practical cases. However, many studies about Prussian blue deposited on nanoparticles have appeared recently in the literature both for environmental and biomedical practical applications [ 34 , 35 , 36 , 37 ]. Prussian blue is also particularly suitable for medical applications, as its toxicity on humans is very modest.…”
Section: Introductionmentioning
confidence: 99%
“…The papers present different nanomaterials such as layered double hydroxides [1]; nanoporous carbon [2]; oxide nanoparticles, i.e., ZnO [3] and MnO [4]; Ag metal nanoparticles [5]; polymer fibers [6,7]; and inorganic BiOCl doped Dy +3 powders [8]. Hybrid materials combining metal organic frameworks (MOF) such as MIL-88A [9] and Prussian blue combined with graphene and carbon nanotubes (CNT) [10], along with magnetic nanoparticles, i.e., magnetite (Fe 3 O 4 ) and ferrite (Mn-Zn) [11], are also featured. These nanomaterials have been applied to the degradation of dyes and pharmaceuticals, along with heavy metal ion and radioactive ion extraction.…”
mentioning
confidence: 99%
“…In addition, graphene played a very important role in enhancing the photocatalytic activity of the material towards the degradation of Rhodamine B dye. The last paper by Rauwel et al is a contribution from the guest editors, and reviews the various hybrid nanomaterials studied by various groups [10]. They focus on the extraction of 137 Cs + from aqueous media in the light of the recent Fukushima Daiichi catastrophe.…”
mentioning
confidence: 99%